Effects of feeder design and pellet quality on finishing pigs - Amornthewaphat, N.; Hancock, Joe D.; Behnke, Keith C.; McKinney, Leland J.; Starkey, C.W.; Lee, D.J.; Jones, C.L.; Park, J.S.; Dean, D.W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pigs fed from wet/dry feeders had 2.5% greater ADG and used 26% less water compared to pigs fed from conventional dry feeders. Also, as percentage fines was increased from none to 50%, ADG and digestibilities of DM and N decreased. However, the decreased ADG with increased pellet fines occurred only with the conventional dry feeder.
Keywords: Swine; Pellet quality; Wet/dry feeders; Finishing pigs